On the steady shear behavior of hydrophobic fumed silica suspensions in PPG and PEG of low molecular weight. Issue 1 (2nd January 2017) - Rubio-Hernández, F. J.; Gómez-Merino, A. I.; Páez-Flor, N. M.; Velázquez-Navarro, J. F.
ABSTRACT: Fumed silica with n-hexadecane molecules anchored onto its surface (Aerosil ® R816) was dispersed in polypropylene glycol of low molecular weight (PPG400). This system showed a complex steady shear behavior: shear-thickening between two shear-thinning regions. Only shear-thinning behavior was observed when R816 was dispersed in polyethylene glycol of low molecular weight (PEG200). To conciliate both experimental results, Raman spectra of linear hexadecane, n-hexadecane/PPG400, and n-hexadecane/PEG200 mixtures were obtained. Results pointed out a distinct population of conformers could exist in each n-hexadecane-polymer mixture. More specifically, alkyl chains acquired straighter conformation in the PPG400 solvent, while the same alkyl chains showed globular conformations in PEG200.